'Ask not what your country can do for you': Legacies of the Great Recession and the consequences of the 'trust crisis' - Alia Aghajanian; Rute Martins Caeiro; Eva-Maria Egger; Patricia Justino; Maria C. Lo Bue (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper investigates how persistent changes in trust caused by the Great Recession have affected how governments and citizens across Europe responded to the next global crisis: the COVID-19 pandemic. We show that increases in individualism and mistrust towards institutions caused by individual exposure to the 2007-08 global financial crisis across European regions shaped citizens' responses to public health policies to curtail the spread of the COVID-19 pandemic almost 15 years later. Contrary to expectations, affected individuals exhibited significantly greater declines in mobility during the initial period of lockdown than others. We attribute this effect to individuals prioritizing their own safety amid perceived breakdowns in the social contract and lack of trust that governments would protect them. Mistrust driven by exposure to the Great Recession has also led to increased discontent of citizens with more traditional European centrist governments. These results suggest that economic events that lead to changes in social trust have lasting legacies by affecting government and citizen responses to future crises.
Keywords: H12; I18; N14; Z18; 330; trust; social contract; Great Recession; Europe; public health policies; COVID-19